PELATIHAN DIGITAL MARKETING UNTUK PENINGKATAN PROMOSI PRODUK UNGGULAN DAERAH BIPANG TANJUNG SAKTI - Puspita, Desi; Putrawansyah, Ferry; Arif, Alfis (FORDICATE, 2022)
The purpose of this activity is to provide students and the Tanjung Sakti community with knowledge about the use of digital marketing as a marketing medium to increase superior products in the Bipang Tanjung Sakti area. Where the development of the world in the digital era is so fast and it is very important for students and the community to use it in a positive direction and not misuse. Having digital marketing skills can become a marketing medium and provide skills in increasing product sales. The methods of implementing the activities carried out are the preparation stage, the implementation stage, the implementation stage and the evaluation stage. This activity is in the form of lectures, discussions, questions and answers and provides digital marketing training for students and the public in an effort to increase the promotion of superior products in the Bipang Tanjung Sakti area as an opportunity to open a business for entrepreneurship. The results of the implementation of activities at the pretest stage with a score of 70% show that many community service training participants still do not know about digital marketing. Next is the implementation stage by providing digital marketing training with materials on Packing, Photography Techniques, and Social Media Promotion. The results of the evaluation of the participants after training on digital marketing materials through protest obtained a value of 93%. This shows that after this training the participants really understand digital marketing to increase the promotion of superior products in the Bipang Tanjung Sakti area